P24 Prevalence of obstructive sleep apnoea in patients scheduled for bariatric surgery and validation of the STOP-BANG questionnaire as a screening tool. (2nd December 2011) - Kaiser, R; Hammond, C; Restrick, L; Branley, H; Lock, S; Sufi, P; Heath, D
Abstract : Background: Obstructive Sleep Apnoea (OSA) is common in morbidly obese patients scheduled for bariatric surgery, and many sleep centres perform routine preoperative sleep studies for all. However a significant proportion will not have significant OSA. Epworth Sleepiness Score (ESS) is unreliable in predicting the risk of OSA. A practical screening tool is ideally required. We aimed to define the prevalence of OSA in our bariatric patient population and validate the STOP-BANG questionnaire as a screening tool. Methods: Retrospective review of bariatric patients who had sleep studies over a 3-month period from January to March 2011. Clinical data collected from medical notes and sleep study results. STOP-BANG scores derived retrospectively from clinical data. Questionnaire included 8 yes/no questions, scored 1 for every yes answer (Abstract P24 table 1 ). A score of 4 or more was considered as high risk for having OSA. STOP-BANG scores were then correlated with sleep study results. Significant OSA (which may require treatment with preoperative CPAP) was defined as a Apnoea-Hypopnoea Index (AHI) of at least >15. Results: Patient characteristics (n=61): mean age 45 (24–69), 87.3% female, mean BMI 46.2 (35–67), mean ESS 6.5 (0–20). Sleep study results – 18% had AHI 15–30, 13.1% had AHI >30. 55.7% had STOP-BANG score of = 4, 44.3% had score of = 3. Of patients with significant OSA (AHI>15): mean BMI 47.2, mean neck circumference 41.4 (SD 2.5), Mean ESS 8.5 (SD 4.84), 66.6% had ESS <11, 89.4% were loud snorers. Using STOP-BANG score of = 4 to screen for OSA with AHI >15—Sensitivity 94.7%, Specificity 61%, positive predictive value 52.9%, negative predictive value 96.2%. Conclusions: 31% of patient population studied had at least moderate OSA. ESS poorly predictive of risk of OSA. Using a high risk STOP-BANG score of 4 had a high sensitivity but poor specificity. However, a low risk score of <4 had a high negative predictive value of 96.2% for AHI >15. Therefore STOP-BANG questionnaire using a cut-off risk score of 4 can be used as a screening tool to rule out significant OSA and thus avoiding sleep studies in a significant proportion of low risk patients.